"Backdoor Induction" of Chirality in Asymmetric Hydrogenation with Rhodium(I) Complexes of Amino Acid Substituted Triphenylphosphane Ligands. Issue 36 (5th November 2013) - Kokan, Zoran; Kirin, Srećko I.
Abstract: This paper describes the synthesis and characterization of 5‐(diphenylphosphanyl)isophthalic acid bioconjugates (Lig‐[R]2 ). In addition to symmetrically disubstituted conjugates with amino acids, peptides or amines, a convenient one‐pot, two‐step procedure for the synthesis of conjugates bearing two different substituents is reported. The 28 prepared phosphanes were used as monodentate ligands in the rhodium(I)‐catalyzed hydrogenation of 2‐acetamidoacrylate and ( Z )‐α‐acetamidocinnamate. The ligand with the smallest side‐chain substituents Lig‐[Ala‐OMe]2 (1a ) revealed the highest selectivity, with up to 84 % ee . The catalysts presented herein are models of artificial metalloenzymes in which the outer‐coordination sphere controls the selectivity in catalysis. The chirality of distant hydrogen‐bonded amino acids is transmitted by "backdoor induction" to the prochiral Rh I center. Abstract : Models of artificial metalloenzymes are presented in which the outer‐coordination sphere controls the selectivity in catalysis. The chirality of distant hydrogen‐bonded amino acids or amines is transmitted by "backdoor induction" to the prochiral Rh I center.